Not Missing the Future: A Call to Action for Investigating the Role of Regenerative Medicine Therapies in Pediatric/Adolescent Sports Injuries. Issue 3 (May 2017) - Best, Thomas M.; Caplan, Arnold; Coleman, Michael; Goodrich, Laurie; Hurd, Jason; Kaplan, Lee D.; Noonan, Ben; Schoettle, Philip; Scott, Christopher; Stiene, Henry; Huard, Johnny
Abstract : In August 2016, a group including sport medicine clinicians, researchers, and a bioethicist met in Vail, Colorado to discuss regenerative medicine and its potential role in youth sports injuries. There was consensus that a call to action is urgently needed to understand the current evidence base, the risks and rewards, and future directions of research and clinical practice for regenerative medicine therapies in youth sports. We present here a summary of our meeting, which was supported by the National Youth Sports Health and Safety Institute (NYSHSI), a partnership between the American College of Sports Medicine (ACSM) and Sanford Health. The group's goal is to educate practitioners and the public, and to pioneer a means of accumulating meaningful clinical data on regenerative medicine therapies in pediatric and adolescent athletes.